DEVELOPMENT OF CREATIVE ABILITIES OF STUDENTS BASED ON EDUCATION OF THE ABILITY TO SCIENTIFIC GENERALIZATION - Mutabar Sayfullaevna Meylieva (Web of Journals Publishing, 2023)
The article discusses the development of students' creative abilities based on cultivating the ability to scientific generalization.
Keywords: evelopment, creativity, abilities, student, basis, education, abilities, generalization.